1977
DOI: 10.1007/bf00345358
|View full text |Cite
|
Sign up to set email alerts
|

Carbon cycling in a loblolly pine plantation

Abstract: The carbon cycle of a loblolly pine plantation in North Carolina was examined during its 12th through 16th years from planting. Net primary production during the study period averaged 2056 g C m year. With autotrophic respiration equal to 2068 g C, the calculated gross production was 4124 g C m year. Heterotrophic respiration of 694 g C m year resulted in net ecosystem production of 1362 g C m year. In carbon cycle comparisons between forest ecosystems, autotrophic respiration rates were found to be closely co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(40 citation statements)
references
References 5 publications
6
32
2
Order By: Relevance
“…Grier et al (1981) and Keyes and Grier (1981) report total Nel' of 15.4 --18.3 t dry wt ha -1 year -1 including above and below-ground production for four sites near Seattle, a reasonable correspondence. Kinerson et al (1977) reported total Nl, e of 20.56 t C ha -1 year -1 for a Pinus taeda plantation, considerably higher than our maximum yap of 14.1, but that NPP is the highest ever recorded. Gholz and Fisher (1982) report aboveground NPP of 12 MT for a Pinus elliottii stand with tAX = 6.5.…”
Section: Net Primary Production-respirationcontrasting
confidence: 74%
See 2 more Smart Citations
“…Grier et al (1981) and Keyes and Grier (1981) report total Nel' of 15.4 --18.3 t dry wt ha -1 year -1 including above and below-ground production for four sites near Seattle, a reasonable correspondence. Kinerson et al (1977) reported total Nl, e of 20.56 t C ha -1 year -1 for a Pinus taeda plantation, considerably higher than our maximum yap of 14.1, but that NPP is the highest ever recorded. Gholz and Fisher (1982) report aboveground NPP of 12 MT for a Pinus elliottii stand with tAX = 6.5.…”
Section: Net Primary Production-respirationcontrasting
confidence: 74%
“…Kinerson et al (1977) found maintenance respiration to be 32% and growth respiration to be 15% of annual photosynthesis for a P. taeda stand in North Carolina. Our most comparable site would be Knoxville at LAI = 6, where maintenance respiration was 22% and growth respiration was 26%.…”
Section: Net Primary Production-respirationmentioning
confidence: 91%
See 1 more Smart Citation
“…For each literature value, the reported initial stand characteristics such as planting density, SI and management activities (site preparation, weed control, fertilization and thinning) were used as model inputs. Loblolly pine's T C , AG C and BG C were validated in two ways, depending on the availability of information: (i) whole-model validation, using reports that included planting density, SI and management activities [25,[41][42][43][44][45][46][47][48]; or (ii) allometry validation, using reports where SI was not reported [27,[49][50][51][52][53]. The former enabled us to run the model from planting year to age when biomass was determined.…”
Section: Model Validationmentioning
confidence: 99%
“…Values for the C contents of plant tissues vary in the literature from 45% to 54% (Kinerson et al, 1977), A conversion factor of 50% is commonly used to estimate the organic C content of plant tissues (Brown and Lugo, 1982;Harmon et al, 1990). Table I TABLE I Biomass components of P. patula and E. grandis in southern Africa at harvest maturity (Christie, 1991;Herbert and Robertson, 1991;Morris, 1992) presents the data used to estimate F tern for typical Pinus and Eucalyptus species growing in plantations in South Africa.…”
Section: Carbon Storage Due To Afforestationmentioning
confidence: 99%